Molecular detection of Leptospira sp. in cattle and goats in Kelantan, Malaysia after a massive flood using multiplex polymerase chain reaction - Sabri, A. R.; Bejo, Siti Khairani; Zakaria, Zunita; Hassan, Latiffah (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Flood is a potential driver in spreading waterborne diseases including leptospirosis, which is a zoonotic disease caused by pathogenic bacteria of the genus Leptospira. In the case of leptospirosis, cattle and goats can be incidental hosts and potential carriers of leptospirosis. Traditionally, serology such as microscopic agglutination test (MAT) and isolation of the organisms have been commonly used as the diagnostic approaches in diagnosing leptospirosis. However, nowadays, various molecular techniques have been developed for specific detection of Leptospira sp. such as, polymerase chain reaction (PCR), which is sensitive, specific and rapid in detecting the species. This study detected Leptospira sp. directly from the blood and urine of the animals such as, cattle, goats and sheep in Kelantan after a massive flood by using multiplex PCR (mPCR). From the results collected in the study, four blood samples (0.63%; 4/635) were found to be positive with Leptospira sp. and one urine sample (3.23%; 1/31) was detected as positive with Leptospira sp. The blood and urine samples that were detected to be positive with Leptospira sp. were collected from cattle and goats exposed to the flood. However, no Leptospira sp. was detected from the sheep in this study. Multiplex PCR (mPCR) was successfully used to detect the presence of Leptospira sp. in animals. Apart from that, it is also suggested that flood has a significant role in transmitting the disease to animals.